Avoidance and restriction of food intake disorder {ARFID) associated with obsessive symptoms in a child with autism spectrum disorder on the subject of a clinical case - Huete-Córdova, María A. (2021)
The case of an 11 years old who is admitted to the pediatric emergency room due to severe dehydration, abdominal pain, vomiting, weight loss, obsessive ideas related to food intake due to fear of vomiting, obsessive concern in relation to food is presented. consumption of some foods rich in carbohydrates for fear of digestive disconfort, denies fear of gaining weight. During hospitalization for severe protein-calorie malnutrition, other non-psychiatric causes are ruled out and the psychiatric evaluation of the child and adolescent obtains characteristic data of autism spectrum disorder and clinical avoidance and restriction of food intake disorder that presented it a lot Previous time, symptoms that went unnoticed despite the decrease in body weight, presenting symptoms of obsessive compulsive disorder (OCD) with a predominance of obsessive thoughts, which aggravated the previous diagnosis. Therefore, pharmacotherapy and individual and family psychotherapy is started, obtaining positive results in the patient. Due to the high prevalence of comorbidities of autism spectrum disorder, such as the case that we present with OCD and TERIA, its identification and pharmacological and psychotherapeutic treatment are important for a better prognosis.